Clinical, hematological, cytological, diagnosis and treatment aspects of transmissible venereal tumor in dog (Research, Society and Development, 2021)
The Transmissible Venereal Tumor (TVT) is a malignant neoplasm, whose transmission is usually sexual, and can also occur by licking or biting. The aim of this study was to report a clinical case of TVT in the genital region of a male dog in the city of Belém, Pará. The diagnosis was based on clinical (clinical history), laboratory (hemogram) and cytological examination. The therapeutic agent used was vincristine sulfate, with a good prognosis in 90% of the cases, when the treatment is carried out correctly. In this case, the treatment proved to be effective and the tumor regressed.